Analysis of The Optical Properties of The Synthesis of Fe3o4/Pani Nanocomposites with The Sol-Gel Method using Spin Coating - Nadya Aztifa; Yenni Darvina; - Ramli; Rahmat Hidayat (Department of Physics – Universitas Negeri Padang UNP, 2023)
Research has been carried out on the analysis of the optical properties of Fe3O4/PANi nanocomposites synthesized by the sol-gel method using spin coating. The purpose of this study was to determine the crystal structure, crystal size, surface morphology, and optical properties of the Fe3O4/PANi nanocomposite thin films. One of the applications of optical properties is that it can be used as a semiconductor. In this study, the primary material used was iron sand obtained from Oyster Beach, Padang Pariaman Regency, West Sumatra. Iron sand contains a magnetite (Fe3O4) phase, which has the highest magnetic properties, and the polymer used is a type of polyaniline polymer (PANi) which has good chemical stability. Fe3O4 acts as a filler, while PANi acts as a matrix. In this study, five variations of the composition of Fe3O4 in PANi were used, namely 30%, 40%, 50%, 60%, and 70%. For the method used, namely the sol-gel method and sample testing using XRD, SEM, and UV-Vis Spectrophotometer characterization tools. The results of the XRD characterization showed that each addition of PANi into Fe3O4 did not affect the resulting crystal structure and had a crystal size below 100 nm. SEM testing revealed the presence of agglomeration and particle size at variations of 30%, 40%, 50%, 60%, and 70% were 27 µm, 53 µm, 61 µm, 84 µm, and 46 µm respectively. And the results of the UV-Vis Spectrophotometer test obtained energy gap values for variations in the composition of Fe3O4 in PANi, namely 30%, 40%, 50%, 60%, and 70%, respectively, namely 2.51 eV, 2.39 eV, 2.18 eV, 2.35 eV, and 2.30 eV. Based on the research results, it can be proven that the Fe3O4/PANi nanocomposite thin layer is a semiconductor material because it is in the range of 0-3 eV.